PROPERTIES OF POLYMERIC ANTIFRICTION COATINGS IN ACID AQUATIC MEDIA - Vadim A. Kokhanovskiy; Vladlen V. Rubanov; Ilya B. Vlasenko (Advanced Engineering Research)
The field research of the adhesion strength and creep flow of the polymeric composite coatings in the acid aquatic media is resulted.